A loucura interrompida nas malhas da subjetividade manicomial - Alverga, Alex Reinecke de (2004)
Psychiatric reform occurring in Brazil has progressed significantly during the last two decades, both in the transformation of the help structure and in the treatment of madness. At the same time a paralell movement is observed marked by the maintenance of the hospital centered or psychiatric ward ideology present not only in the psychiatric institutions but also in the substitute services in the cities and , above all, in the ways of contemporary subjectivation. We affirm that the idea of deinstitutionalization is intertwined with capitalistic agent both from the epistomological, assistance, and legal aspect as from the cultural one. This work aims mainly to discuss madness and subjectivity from the ethic esthetic-political perspective, specially the wishes of the psychiatric hospital, which we inhabit and who inhibits our interactions and our desired and creative productivity. We do also want to access the invisible threads that capture and modify madness, which make our cities a means for the production of pathologies, and those that, on the contrary, insinuate a process of resistance, facilitating life and health